2018
DOI: 10.18410/jebmh/2018/490
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Histopathological Study of Thyroid Lesions in a Tertiary Care Center Over a Period of One Year

Abstract: BACKGROUND Thyroid nodules are common in clinical practice, occurring globally with wide variation in incidence and histopathological pattern related to age, sex, dietary and environmental factors. This study was undertaken to describe the spectrum, frequency, age, sex distribution and various histopathological patterns of thyroid lesions. MATERIALS AND METHODS The present study is a hospital based prospective observational study conduted for a period of one year from January 2017 to December 2017, and was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…A considerable number of the cases in this study were non-neoplastic thyroid lesions constituting 419 cases (88%) of the cases. This observed significance of non-neoplastic lesions in our study is in accord with findings from sravani et al, 13 Chung et al 22 and Hill et al 23 which was 62.5%, 84.1% and 60.5% respectively.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A considerable number of the cases in this study were non-neoplastic thyroid lesions constituting 419 cases (88%) of the cases. This observed significance of non-neoplastic lesions in our study is in accord with findings from sravani et al, 13 Chung et al 22 and Hill et al 23 which was 62.5%, 84.1% and 60.5% respectively.…”
Section: Discussionsupporting
confidence: 94%
“…Both the neoplastic and non-neoplastic diseases of thyroid are common all over the world, with diversity in frequency and incidences depending upon iodine deficiency status. 11 In our present study, the age of the patients ranged from 10 years to 80 years with a mean age of 47 years which was similar with the study of Arvintham, 12 Urmila devi et al, 13 Silverman 14 et al and which were lower when compared with study conducted by Sathiyamurthy 15 In our present study the commonest age group presenting with thyroid disorders was in the 4 th to 5th decade which was correlating with the study by sreedevi 3 et al while study carried out by Jagadale K et al 16 and Ramesh V L et al 17 was found to be 4th to 6th decades and 3rd to 5th decade respectively. In the present study, it was observed that 408 (85.7%) cases were females and 68 (14.2%) cases were male.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our observation the incidence of non-neoplastic thyroid lesions as published in various studies has been reported to range from 62.5% to 84%. 1 , 3 , 4 – 7…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Lymphocytic thyroiditis was observed up to 1% and 15% in studies. 4 , 8 While Hashimoto's thyroiditis was witnessed as high as 9.1% to 14%. 4 , 8 , 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation